Hak-Hak Anak yang Dirampas Kajian terhadap Kasus Perdagangan dan Eksploitasi Anak dalam Sudut Pandang Ham dan Islam - Syamsul Kurniawan (PSGA LP2M IAIN Pontianak, 2017)
The case of trafficking and exploitation on children has become significant problems in Indonesia. The news released by KPAI in 2012, for instance, concluding that the number of trafficking and exploitation on children is slightly high. Furthermore, the police of West Kalimantan has displayed 14 cases of human trafficking and arrested 20 perpretrators from January to September 2016, while some of the victims are children. Moreover, the writer has interviewed some children in Pontianak City that work as maids, polishers, newspaper sellers, street singers, beggars, and so forth, that is caused by economic reason. Besides, the children trafficking and exploitation could be grouped as a humanity crime. Therefore, the writer has an interest to analyse this case related to human rights and Islamic point of view.